Domínios de Dirichlet e de Ford de subgrupos cíclicos de PSL(2,C) agindo na fronteira do espaço hiperbólico tridimensional - Rejane Izabel Lima Correa (2010)
Let  be a cyclic subgroup of PSL(2; ) generated by an element loxodromic. The fundamental domain of Ford and Dirichlet for the action of   in H^3 are complementary to a configuration of semi-spheres centered at =H3. Jorgensen showed that the boundary of the intersection of the fundamental domain of Ford with H3 always has two, four or six sides formed by circular arcs. In this work we are interested in extending the result shown by Jorgensen for the Dirichlet fundamental domain. Analyze the fundamental domain for Ford and Dirichlet, and demonstrate some combinatorial properties of these domain that will demonstrate that their intersections with H3 always have two, four or six sides.